Improving Online Learning Through Zoom Meeting Media In Class 2nd at SD Muhammadiyah Bantul City - Maya Kartika Sari; Vivi Rulviana; Suyanti Suyanti (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2022)
This study aims to determine the improvement of online learning through Zoom Meeting media at SD Muhamadiyah Bantul City, especially grade 2nd in elementary school. This type of research is qualitative with a case study approach. Sources of data in this study were grade 2nd teachers, students and parents of grade 2nd at SD Muhammadiyah Bantul Kota. Data collection techniques using interviews, observation, and documentation. Data analysis used triangulation of data sources. The results showed an increase in student learning in the form of increasing student understanding in receiving subject matter, students enjoying learning more, teachers and students can interact directly through zoom meetings, foster student interest in learning, teachers can better understand the character of students, students can work on practice questions with good, and parents can unite student learning to be more optimal